2012
DOI: 10.1177/1477370811424985
|View full text |Cite
|
Sign up to set email alerts
|

Shades of professionalism: Risk assessment in pre-sentence reports in Sweden

Abstract: An emphasis on risk assessment has been introduced in the instructions guiding pre-sentence reports in Sweden. Since this focus indicates an organizational aspiration to risk management, we examined how pre-sentence assessments are made and especially how probation officers relate to risk assessments. Our results show that probation officers do not act in accordance with the guidelines; they tend to focus on offender needs and social situations more than risk factors, and the reports still resemble the previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 19 publications
0
16
0
2
Order By: Relevance
“…On average, 62% of the factors listed in Table 1 were addressed one way or the other in the investigations supported by the SAVRY, compared to 48% and 42% for ADAD and IAU investigations, respectively. This is an important finding, because it shows that the SAVRY can be a means to counter a tendency among social workers to focus on clients general needs and social situations rather than on empirically founded risk and protective factors (Persson & Svensson, 2012; see also Andershed & Andershed, 2015).…”
Section: Discussion and Applications To Practicementioning
confidence: 95%
See 1 more Smart Citation
“…On average, 62% of the factors listed in Table 1 were addressed one way or the other in the investigations supported by the SAVRY, compared to 48% and 42% for ADAD and IAU investigations, respectively. This is an important finding, because it shows that the SAVRY can be a means to counter a tendency among social workers to focus on clients general needs and social situations rather than on empirically founded risk and protective factors (Persson & Svensson, 2012; see also Andershed & Andershed, 2015).…”
Section: Discussion and Applications To Practicementioning
confidence: 95%
“…First, in agreement with the few previous studies of the SAVRY in naturalistic settings, this study showed that regular practitioners are able to conduct valid risk assessments when using a structured instrument. This conclusion may be of special interest in Sweden, because of recent claims that Swedish social workers are unable to properly assess risk due to inadequate education and training (Persson & Svensson, 2012). Hence, our conclusion is that it is not the competence, but rather the proper methods, that are lacking.…”
Section: Discussion and Applications To Practicementioning
confidence: 98%
“…In most of the criminal justice systems where the probation service is established, one of its core duties is the analysis of the defendants' personality, trough creation of the risk evaluation schemes 19 . Performance of the risk evaluation is particularly important for the courts while deliberating the most appropriate measure for providing defendant's presence during the criminal trial, or sanction at the end of the criminal trials.…”
Section: Probation Services During the Criminal Procedures And Implemementioning
confidence: 99%
“…Elle a également un lien avec les discriminations et biais des magistrats, encore qu'il arrive que les rapports présentenciels censés les contrebalancer soient eux-mêmes contaminés par de telles discriminations et biais (Hannah-Moffat et Maurutto, 2010;Power, 2003 ;Leiber et al, 2011), notamment des biais pénologiques (nouvelle pénologie répressive) manifestes (Field et Tata, 2010). Toutefois, une série de recherches scandinaves a montré que les rapports présentenciels demeurent un outil particulièrement intéressant de lutte contre les courants répressifs actuels (Wandall, 2010;Persson et Svensson K, 2010;Persson et Svensson, 2011). Ces rapports doivent cependant trouver un juste équilibre entre professionnalisme et présentation objective des faits car les magistrats n'aiment guère que leurs auteurs tentent de les manipuler ou de s'approprier la décision finale (Tata et al, 2008).…”
Section: L'émotion Et Son Contrôle Par L'informationunclassified